Visualizing and Testing Convergence Between Two Income Distributions - Bishop, John A; Chow, K. Victor; Zeager, Lester A. (Journal of Income Distribution®, 2009)
We use the Interdistributional Lorenz Curves (ILCs) of Butler and McDonald (1987) to visualize convergence or divergence between income distributions. To illustrate the idea, we compare income distributions from Spain, Italy, and Germany. We also offer methods to test for significant differences between the 45-degree line and an ILC, or between ILCs in different years. The tests apply to any partial moment of the distributions and impose no prior restrictions on the functional form of the underlying distribution. We illustrate the statistical inference tests by an application to income distributions for whites and non-whites in the United States.